Electronic Patient-Reported Outcome Measure and Decision Support Tool Option for Early Intervention Service Quality: A Pilot Cluster-Randomized Pragmatic Trial. - Kaelin, Vera C.; Rizk, Sabrin; Chen, Yi-Fan; Dooling-Litfin, Jodi; Lerner Papautsky, Elizabeth; Leland, Natalie E.; Murphy, Natalie J.; McManus, Beth M.; Lage, Carla R.; Villegas, Vivian; Kuznicki, Lindsay; Pedrow, Amanda; et al. (Advances in Rehabilitation Science & Practice, 2026)
Introduction: The Young Children's Participation in Environment Measure (YC-PEM) is an evidence-based and promising electronic patient-reported outcome (e-PRO) option to improve early intervention (EI) service quality, such as when designing the EI service plan. Aim: Establish the preliminary effectiveness of implementing the YC-PEM e-PRO and program-specific shared decision support tool option for EI service quality when designing a service plan. Methods: For this 2-arm pilot pragmatic trial with cluster randomization at the provider level, 76 caregivers enrolled and 57 caregivers (n = 29 intervention group; n = 28 control group) completed pre- and post-intervention measures. Intervention group caregivers completed the YC-PEM e-PRO and program-specific shared decision support tool and were compared to usual care on EI service quality indicators: (1) caregiver perceptions of family-centeredness, (2) caregiver activation for shared decision-making, (3) caregiver engagement in service design and implementation; and (4) service plan quality. Results: No significant group differences at baseline were noted. Pre-post EI service quality revealed no significant differences in the adjusted model (P >.05). However, intervention group families had higher rates participation-focused service plans (69.2%) versus controls (51.4%), most of which met state-level criteria for quality (84%). Conclusion: For EI service quality indicators, this intervention option demonstrated comparable performance to usual care. This finding suggests the intervention promoted high quality, participation-focused service planning despite no overall differences in EI service quality, warranting further testing of implementation factors and effectiveness in various service contexts. Trial Registration Number: NCT04562038